One new luminous mushroom species for the macrofungi flora of Vietnam Mycena chlorophos (Berk.: Curt.) Sacc. - Tham, Le Xuan (Academia Journal of Biology, 2014)
The new luminous mushroom species Mycena chlorophos (Berk.: Curt.) Sacc. for the macrofungi flora of Vietnam was found in the Cattien national park, Dongnai province, South Vietnam. They grew as saprophytic clusters, quite translucent and ivory-white on rotten bamboos and leaves. Morphological features of the fruit bodies (2.3-5.6 cm in diameter of pilei and 1.8-5.7 cm in length of stipes) were described in details with sophisticated illustrations of the authentic specimens, particularly collected showing their bioluminescent ability to emit steadily a beautiful pale green light in dark nights of the rainy season (May-August). The pilei hemisphere-applanate conico-convex - applanocampanulate, radially sulcate-striate, hygrophanous, translucent-striate, minutely white-ivory pruinose at first, glabrous in age, translucently white-ivory overall or often fuliginous at the apex. Flesh thin (up to 1 mm), translucent, hygrophanous, fragile. Stipes cylindric, slightly enlarged at the base, central, slender, more or less hollow, translucently white above, fuliginous toward to the base, white pruinose over the entire length, white strigose at the base. Lamellae adnate-decurrent, crowded, thin, up to 2.7-3.2 mm broad, ivory white; edges pruinose, concolorous. Spore print chalky white. Basidiospores ellipsoid, 8.2-11.4 ´ 4.6-5.8 mm, smooth, colorless - translucent with some guttules, thin-walled. The attractive luminescent appearances of the fruit bodies (only from the pilei but not from the stipes) were observed both in young to old development stages (during 3-4 days in every flushes).